Progress in Research and Application of Plant-Based Fermented Milk - MA Xiaoyan, WAN Xia, CHEN Yashu, ZHANG Mengke, WANG Chao, DENG Qianchun (Shipin Kexue)
The market for functional and nutraceutical foods is one of the fastest growing markets in the new food creation area, especially in the era of great health. Because of its nutritional and functional qualities, plant-based fermented milk has great development prospects. This review summarizes the quality characteristics of plant-based raw materials, probiotic fermentation characteristics, and the effects of probiotics on the flavor, nutrition and gel stability of plant-based fermented milk during the fermentation process. Additionally, we discuss future prospects for the development and application of plant-based fermented milk. This review aims to offer scientific guidelines for the production of high-quality plant-based fermented milk.